Factors that influence the external potential of Islamic education management; Government Policy, Technological Development and Socio-Cultural Society - Rois Amin, Mursyid Musthofa An Najmi; Ali, Hapzi; Imron Rosyadi, Kemas (International Journal of Advanced Multidisciplinary, 2023)
Factors that influence the external potential of Islamic education management, Government Policy and Technological Development on Socio-Cultural Society is a scientific article of literature study within the scope of the field of science. The purpose of this article is to build a hypothesis of the influence between variables that will be used in further research. Research objects in online libraries, Google Scholar, Mendeley and other academic online media. The research method with the research library comes from e-books and open access e-journals. Qualitative descriptive analysis. The results of this article: 1) Government policies affect the external potential of MPI; 2) Technological developments affect the external potential of MPI; and 3) Socio-cultural influences on the external potential of MPI;